A qualitative analysis of Ethiopian and Eritrean Americans' initiation and continuation of hookah smoking. Issue 1 (1st February 2023) - Kidanu, Azieb W.; Kidanu, Tamnnet W.; Butler, James; Dyer, Typhanye V.
Abstract: Hookah smoking is emerging as a popular social practice and health behavior risk among Ethiopian and Eritrean Americans. This qualitative study was the second phase of a sequential exploratory mixed methods study and examined factors that enable the initiation and facilitate the continuation of hookah smoking among Ethiopian and Eritrean Americans. Semi-structured interviews were conducted with twenty-five Ethiopian and Eritrean American hookah smokers residing in the Washington, DC Metropolitan Area of the United States. Interview questions were guided by the Theory of Planned Behavior and addressed: (1) initiation of hookah smoking, (2) past and current patterns of hookah smoking, and (3) behavioral, control and normative beliefs toward hookah smoking. Several themes were identified under the core constructs of 'factors influencing hookah smoking initiation' and 'factors influencing hookah smoking continuation' such as curiosity, lack of health knowledge, socio-cultural acceptance, accessibility, flavor, physical dependence, physiological effects and social connections. Based on these findings, it is recommended that future prevention activities (e.g. health messages) be embedded into a comprehensive tobacco prevention approach to address individual misperceptions of harm and addiction, community social norms and environmental access around hookah smoking, which contribute to both initiation and continuation in the Ethiopian and Eritrean American populations.